SISTEM PENGENDALIAN PERSEDIAAN STOK BAHAN BAKU MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY DI PIZZAHUT SETIABUDI - Cindy Anindya Puspadev (Teknik Informatika, 2021)
Pizzahut Setiabudi Semarang is a middle class restaurant in Indonesia that serves pizza, pasta and also various kinds of food. The process of recording stock inventories at Pizzahut Setiabudi currently still uses manual recording on books, both incoming and outgoing materials. In addition, the procurement process for raw material stock only uses estimates, this can lead to excess stock in the warehouse or actually experience a stock shortage which can later hamper the operational process of the business. In this research, we build a raw material inventory control system to help restaurants manage material stock data using the Economic Order Quantity (EOQ) method. EOQ is a method used to optimize the purchase of raw materials that can reduce inventory costs so that the efficiency of material inventory in the company can run well.